The Legitimacy of Maqāsid Shariah on the Islamic Turath in the Tradition of Reading Yasin Fadhilah at Pesantren Al-Anwar-3 - Abdullah Mubarok; Ali Ja'far (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2022)
Turath is the product of Muslim thoughts from generation to generation, and the Turath should be legitimized. The legitimacy of truth is crucial to confirm the validity of the tradition. Since its source is other than the Qur'an and hadith, Turath is still debatable. Turath criticism is part of the attitude that must be done for the legitimacy of Turath. This practice has the potential to be non-Islamic. Among the Turath practices that need to be legitimized by legal arguments is the method of reading Yasin Fadhilah at the Al-Anwar III Islamic Boarding School. This study of the legitimacy of Yasin Fadhilah's practice uses the views of Ibn 'Ashur with his maqasid shari'ah theory. Research from the maqasid shari'ah perspective will accomplish the view of making law from all sides. Yasin Fadhilah is a tradition of praying with the intermediary of a Yasin chapter carried out based on orders from a teacher from the ahlul-bait of the Prophet Muhammad. From the perspective of Maqasid Shari'ah, the practice of reading the chapter is legal in Islamic law, even though it is included in the Tahsiniyyāt category.